2020
DOI: 10.3390/atmos11030232
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Drivers for Cambial Reactivation of Qilian Junipers (Juniperus przewalskii) in a Semi-Arid Region of Northwestern China

Abstract: Although cambial reactivation is considered to be strongly dependent on temperature, the importance of water availability at the onset of xylogenesis in semi-arid regions still lacks sufficient evidences. In order to explore how environmental factors influence the initiation of cambial activity and wood formation, we monitored weekly cambial phenology in Qilian juniper (Juniperus przewalskii) from a semi-arid high-elevation region of northwestern China. We collected microcores from 12 trees at two elevations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition to temperature, the length of the growing season determines the available period for developing functional xylem through cell maturation and lignification, especially in cold areas 31,33 . In drier ecosystems, water availability for roots, rather than rainfall per se, is another important driver of cambial reactivation 34 . Temperature and the availability and demand of water also codetermine the rate of growth [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to temperature, the length of the growing season determines the available period for developing functional xylem through cell maturation and lignification, especially in cold areas 31,33 . In drier ecosystems, water availability for roots, rather than rainfall per se, is another important driver of cambial reactivation 34 . Temperature and the availability and demand of water also codetermine the rate of growth [35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated by numerous studies that the onset of xylem phenology in cold and temperate ecosystems is mainly triggered by temperature, according to either the accumulated heat sums or critical threshold temperatures [11,21,[27][28][29], indicating that the initiation of cambial activity occurs when the cambium reaches an appropriate thermal condition. In a cold and arid region of the northeastern Tibetan Plateau, the warm spring could advance the cambial resumption of Juniperus przewalskii independently of the rain events that occur before the growing season [28,30]. Rossi et al [25] proposed that spring temperatures (April and May) produced the best models to predict the timings of xylem phenology in conifers growing in the cold environment of the northern hemisphere.…”
Section: Effect Of Temperatures On the Onset Of Xylem Phenologymentioning
confidence: 99%
“…There are also differences in the uptake strategies of SM by trees in different moisture environments [8]. Some studies have found that the SM plays a role in tree growth on the Tibetan Plateau (TP) [9,10], especially during the growing season [11]. Unfortunately, it is not practical to collect soil samples when conducting large-scale studies, making it exceptionally difficult to use measured soil data to study tree water use strategies.…”
Section: Introductionmentioning
confidence: 99%